Penerapan Model Pembelajaran Scramble dalam Meningkatkan Aktivitas dan Hasil Belajar Matematika Pada Peserta Didik Kelas V SD - Reski Setia Amalia; Muhammad Ilham; Muh Syarwa Sangila (IAIN Kendari, 2020)
This study aims to improve students' mathematics learning activities and outcomes by applying the Scramble-type cooperative learning model in grade V SDN SATAP 02 Konsel in the 2019/2020 school year. This type of research is a classroom action research conducted in two cycles. The PTK Kurt Lewin Scheme was used in this research which includes planning, implementation, observation and reflection. Data collection techniques were observation sheets, tests, and documentation which were analyzed descriptively. The results showed that the application of the Scramble learning model can improve the learning activities of class V SDN SATAP 02 Konsel. The results of the observation sheet activity of students in cycle I was 67%, then increased to 86% with the Very Good category in the cycle two. Besides, the use of such method can improve the results of students’ mathematics learning. Before the treatment, the average students’ learning score was 64.46 with 60% completeness. After the first cycle, the average learning score reached to 77.25 with completeness of 75%. Then the learning outcome rose to 82.25 with 81.25% completeness in cycle II.Keywords: Scramble, Aktivitas belajar, Hasil belajar Matematika